Radiological and Audiological Outcomes of the LISTENT LCI-20PI Cochlear Implant Device. Issue 4 (April 2021) - Tan, Haoyue; Yao, Junji; Li, Yun; Zhang, Zhihua; Chen, Ying; Huang, Meiping; Sterkers, Olivier; Jia, Huan; Wu, Hao
Abstract : Objective: To study the surgical results, intracochlear position of the electrode array (EA) and auditory performance of the LISTENT LCI-20PI cochlear implant device, and daily use status at 3 years. Study Design: A retrospective study. Setting: A single-tertiary referral center. Patients: Between January and December 2016, 20 patients underwent cochlear implantation using the LISTENT LCI-20PI (lateral wall EA). Intervention: Cochlear implantation. Main Outcome Measures: Measurement of cochlear size, extent of posterior tympanotomy, and insertion depth. Scalar position of the EA evaluated by 3D reconstruction. Auditory outcomes 1 year after implantation and daily use status at 3 years. Results: EAs were completely inserted in all cases with an insertion depth of 288 ± 36.8 degrees. One year later, the average sentence recognition score (SRS) was 90 ± 21.7%. EA scalar location was analyzed in 18 patients. Thirteen EAs (72.2%) were fully inserted into the scala tympani (ST) and 5 (27.8%) had shifted from the ST to the scala vestibuli (SV). There was no statistically significant difference in cochlear size, extent of posterior tympanotomy, or insertion depth between these two groups. EAs inserted by cochleostomy had a higher chance of scalar shift than those inserted via the round window (60% vs 15.4%, p  = 0.099). SRS at 1 year with full ST insertion was significantly better than in those with scalar shift (99 ± 1.3% vs 83 ± 16.5%, p  = 0.002). Three years after implantation, 92% of patients were daily users and 46% were telephone users. Conclusions: The LISTENT LCI-20PI provided accredited hearing rehabilitation with a short insertion depth. Full insertion into the ST was associated with better cochlear implantation outcomes.